Report on: Training Tomorrow’s Agri-Experts in Sudan - Devkota, Krishna; Devkota Wasti, Mina Kumari (International Center for Agricultural Research in the Dry Areas, 2023)
In Sudan, capacity development of agricultural scientists is imperative for the sustainable development of agricultural sector. As Sudan's agriculture is facing increasingly complex challenges, capacity development of agricultural scientists is essential for sustaining food security, environmental sustainability, and economic growth. By empowering 2 nd generation agriculture scientists and professionals, Sudan can transform its agricultural landscape, ensuring resilient and prosperous future generations. Capacity development of the national researchers and extensionists in statistical analysis of research data, yield gap analysis, participatory research methodologies, and multi-criteria trade-off analysis are crucial for improving research and development quality and progress monitoring.